Microalgae cultivation in stabilized landfill leachate for simultaneous treatment and biomass production - Liew, Li Wen (2023)
Landfill leachate is highly toxic and requires treatment before being released into the environment. Thus, an economical and eco-friendly solution is required. In recent years, microalgae treatment has emerged as an alternative to other conventional treatments as they have high nutrient recovery abilities and potential for bio-fuel production. However, high concentrations of inhibitory compounds and ammoniacal nitrogen in young landfill leachates require high dilutions for microalgae to thrive. This study aims to evaluate the performance of microalgae using stabilized landfill leachate instead with lower to no dilutions in nutrient removal, biomass and lipid production. Leachate concentration of 33v/v%, 44v/v%, 66v/v%, 89v/v% and 100v/v% were treated with the microalgae C. vulgaris. Parameters of Chemical Oxygen Demand (COD), ammoniacal nitrogen (NH3–N), orthophosphate (PO4 3- ), total phosphorus (TP) and colour removal were evaluated. Highest removals of 43.67% for COD, >97.00% for NH3–N, 79.26% for PO3 3- , 77.64% for TP and 44.04% for colour were achieved. Highest biomass yield obtained was 220 mg/L by 89v/v% leachate concentration with 8.14% lipid yield. It is possible to treat stabilized landfill leachate without any dilutions using microalgae, as they can survive the conditions, perform nutrient removals and produce biomass simultaneously.